Chronic endometritis in the development of abnormal uterine bleeding, endometrial dysfunction and other reproductive disorders (literature review) - Rina U. Mitrelis; Liudmila M. Mikhaleva; Mekan R. Orazov; Sergey A. Mikhalev; Tatyana Yu. Kobyzeva (LLC "MEDIAFORMAT", 2024)
Abnormal uterine bleeding (AUB), common in a cohort of women in the reproductive period, is undoubtedly an extremely important factor reducing quality of life. Persistent endometrial inflammation is a pathogenetic link associated with endometrial dysfunction. The article reflects the modern paradigm of etiology, pathogenesis and management of patients with AUB on the background of chronic endometritis according to the data of domestic and foreign literature.